Human spinal enthesis comparative biology of IL-17F and IL-17A reveals greater T-cell IL-17F induction and IL-23 regulation - McDermott, Nicole; Altaie, Ala; Macleod, Tom; Bridgewood, Charlie; Loughenbury, Peter; Dunsmuir, Robert; Khan, Almas; Borse, Vishal; Rao, Abhay; Manghera, Avneet; Shaw, Stevan; McGonagle, Dennis (Frontiers in Immunology, 2025)
ObjectiveAlthough IL-17F is important in psoriasis, the rudimentary biology of IL-17F in the human enthesis remains undefined. We aimed to characterise IL-23-dependent and independent IL-17F production from entheseal innate and adaptive T cells and determine the impact of IL-17F on entheseal stromal function and mesenchymal stem cell (MSC) osteogenesis.MethodsAnti-CD3 and anti-CD28 activated human spinal entheseal T cells were immunophenotyped using multi-parameter flow cytometry and a 36-marker Cytometry by Time-Of-Flight (CyTOF) with cytokine profiling, including IL-17A, IL-17F, and TNF (n = 10). IL-17A, IL-17F, and TNF stimulation of entheseal MSC stromal function was evaluated using RNA-seq and by measuring CCL20 protein expression following stimulation with TNF in combination with IL-17A or IL-17F. The osteogenic effects of IL-17A and IL-17F on MSC differentiation were assessed.ResultsInducible IL-17A and IL-17F expression was predominantly from CD4 T cells and CD4+CD25+ T cells, with higher levels of IL-17F at 72 hr. IL-23 significantly increased IL-17F (p ≤ 0.0001) but not IL-17A. Either IL-17A or IL-17F in combination with TNF dramatically upregulated CCL20 protein expression and substantially changed entheseal stromal transcriptome, with differences in gene expression and pathway activation seen between IL-17A or IL-17F stimulation. However, entheseal MSC osteogenesis was not significantly changed.ConclusionsThere was differential induction of IL-17A and IL-17F from innate and adaptive entheseal T cells, with further significant IL-17F augmentation by IL-23, but not IL-17A. Furthermore, the synergistic effects of IL-17A or IL-17F and TNF on stromal function provide the basis for further enthesis IL-17F biology interrogation.